Food processing technology : Principles and practices - Fellows, P. J. (Cambridge, UK Woodhead, 2017)
This book includes an overview of the component subjects in food science and technology, processing stages, important aspects of food industry management not otherwise considered (e.g. financial management, marketing, food laws and food industry regulation), value chains, the global food industry, and over-arching considerations (e.g. environmental issues and sustainability).
Includes bibliographical references and index
Keywords: Công nghệ thực phẩm